A facile strategy to construct binder-free flexible carbonate composite anode at low temperature with high performances for lithium-ion batteries. (20th August 2017) - Shi, Shaojun; Zhang, Ming; Deng, Tingting; Wang, Ting; Yang, Gang
Graphical abstract: The schematic illustration of the strategy for preparations and the mechanism for the stability of structure Highlights: A facile strategy is applied to construct flexible carbonate composite anode. Carbon nano-fiber matrix serves as fast charge channel and efficient buffer. High specific capacity of 958 mAh g −1 at 100 mA g −1 is obtained. After 200 cycles at 1 A g −1, there is not obvious capacity decline. The mechanism for stress release is further analyzed. Abstract: High temperature is usually necessary for carbon modification or electrospinning to obtain flexible anode with excellent conductivity and stability. However, due to the unstable instinct of carbonate, it's hard to obtain carbonate when any of the synthesis process undergoes high temperature treatment. Thus, a facile strategy is applied to construct binder-free flexible carbonate composite anode at low temperature with high electrochemical performances. The carbon nano-fiber matrix is first synthesized through electrospinning followed by a facile solvothermal process to in-situ grow carbonate on carbon nano-fibers to form a well combinative flexible anode. The carbon nano-fiber matrix serves not only as a fast channel for charge transfer, but also as an efficient buffer to release the stress resulting from the hysteresis of lithiation for carbonate particles during repeated charge/discharge cycles. Owing to the synergistic effect of carbon nano-fiber and the carbonate, the flexible anode exhibits high specific capacity of 958 mAh g −1 . And after 200 cycles at 1 A g −1, no obvious capacity decline. The reaction mechanism for stress release is also well analyzed to display the merit of our strategy. It is considered as one of the most promising way to get binder-free flexible carbonate anode with remarkable properties.